FORMATION OF AN ATHLETE’S MEDIA BRAND THROUGHOUT THEIR CAREER BASED ON SHORT VIDEO FORMATS (REELS, TIKTOK) - IVANYTSKYI, Nazarii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the process of forming an athlete’s media brand in the context of the digitalization of the sports industry, with a particular focus on the use of short video formats (Reels, TikTok). The relevance of the problem is substantiated by growing competition for audience attention and the increasing role of social media in athletes’ career and commercial development. Drawing on an analysis of scientific publications and current digital communication practices, the paper proposes a stage-based model of athlete media brand development comprising the initial, growth, popularity and transformation stages (after the end of active sports participation). For each stage, the main communication objectives, the dominant types of video content and the specific features of using short video formats are characterised.The article identifies the key types of content (performance-oriented, training-process, behind-the-scenes, value-driven personal stories, educational and commercial/partner content) and demonstrates their role in building a coherent and emotionally engaging brand narrative. Practical recommendations are formulated for athletes, coaches, managers and SMM specialists on how to design and implement a content strategy in Reels and TikTok, taking into account the career stage and target audience expectations. The paper also outlines directions for integrating individual athlete media brands into the broader communication strategies of sports organisations. Prospects for further research are defined, including empirical testing of the proposed model in different sports and countries, as well as the study of psychological and ethical aspects of intensive media presence and long-term self-branding in social networks.
Keywords: athlete’s media brand; personal branding; sports marketing; , digital communications; short-form video; Reels; TikTok; social media